Trends in Hospitalization and Mortality Rates Associated with Subarachnoid Hemorrhage and Unruptured Cerebral Aneurysms in Brazil - Poliseli, Gianfelipe Belini [UNESP]; Santos, Thiago Araújo dos [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Victória, Cassiano [UNESP]; Zanini, Marco Antônio [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP] (Elsevier, 2024)
Background: Epidemiology of spontaneous subarachnoid hemorrhage (SAH) and unruptured intracranial aneurysm (UIA) is valuable for determining neurosurgical and general health care effectiveness. There is an information gap regarding these conditions in middle- and low-income countries. Therefore, we aimed to investigate hospitalization and mortality rates for SAH and UIA in Brazil from 2011 to 2019. Methods: This observational, population-based study used hospital admission and mortality data and included all SAH- and UIA-related public hospitalizations and deaths occurring from 2011 to 2019. Data were obtained from the Ministry of Health National Hospitalisation and Mortality Information Systems. Population data were obtained from the Brazilian Institute of Geography and Statistics. Simple linear regression models with normal responses were adjusted to explain the temporal evolution of variables. Joinpoint regression models were adjusted to detect moments of significant change in variable behavior. Graduated choropleth maps were generated using georeferencing and geospatial analyses. Results: Annual SAH hospitalization and mortality coefficients were 4.81/100,000 and 2.49/100,000 persons, respectively. UIA hospitalization and mortality coefficients were 1.21/100,000 and 0.24/100,000 persons, respectively. In addition to regional differences, we found a stable SAH hospitalization trend and an increasing mortality rate of 0.062 cases/100,000 inhabitants annually. The UIA hospitalization rate increased by 0.074 cases/100,000 inhabitants annually, and mortality decreased by 0.07 deaths/100,000 inhabitants annually. Conclusions: In Brazil, the SAH hospitalization trend is stable, although there is a worrisome increasing SAH-related mortality trend. A better scenario was observed for UIA, with an increase in hospitalizations and decrease in mortality.
Keywords: Hospitalization; Mortality; Subarachnoid hemorrhage; Unruptured intracranial aneurysm